A novel method to design pressure compensator for variable displacement axial piston pump. (April 2019) - Mondal, Nitesh; Saha, Rana; Mookherjee, Saikat; Sanyal, Dipankar
An innovative design procedure has been formulated by developing a mathematical model for the pressure compensator of an axial piston pump. The compensator provides energy saving by making the pump variable displacement type depending on the system load, thereby providing energy saving by better resource management. The procedure involves simple static design steps to ensure a balanced swiveling torque on the swash plate for specified cut-in and cut-off pressure limits. Adopting the basic pump model from the earlier works, the dynamic model of the pump has been updated by including the compensator dynamics. A design sensitivity analysis through dynamic simulation has been performed that corroborates the need of the design through torque balancing. Also, through dynamic simulation, tolerances of some critical dimensions have been identified. The pressure compensator model has been validated against experimental result obtained from a reference pump.